Tinjauan Elemen Desain pada Dunia Seni - Aris Darisman (Humaniora, 2012)
Article is a review respected to the elements that are very familiar not even be released in the culture and the visual language–especially the world of art: line, shape, mass, color, value, space, motion. The discussion is limited to the issue of lines because it is one of the most important visual elements and fundamental. The purpose of research is to trace the application of visual elements in art. The methodology used is library research, experiences, and comparative works. Results and discussion form of qualitative analysis. So, it can be concluded that there is a deduction about correlation and function of the visual elements in the art world.